Analysis of Mutation and Turnover Intention: Work Environment - Sameer Seth (Dinasti Publisher, 2022)
The article Literature Review of Mutation Analysis and Turnover Intention: Work Environment is a scientific article that aims to build a research hypothesis on the influence of variables that can be used in further research. The writing method used in this study is the library research method, the sources of which come from Google Scholar, Mendeley, and previous articles that are relevant to this research. The results of this study are: 1) The work environment is related to mutations; 2) The work environment is related to Turnover Intention; and 3) Mutations related to Turnover Intention. Apart from the exogenous variables above that affect endogenous variables, there are other factors including leadership, wages and coworkers.